2006
DOI: 10.1002/ca.20420
|View full text |Cite
|
Sign up to set email alerts
|

The pillars of the scapula

Abstract: Total shoulder replacement has been shown to provide predictable pain relief and functional improvement in patients with glenohumeral arthritis. Loosening of the glenoid component remains the most frequent indication for revision surgery at long-term follow-up. The component most widely used is an all-polyethylene keeled or pegged design cemented to the glenoid cavity of the scapula. The glenoid is small and its cup-shaped morphology allows only a restricted site for limited fixation devices. This is particula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
24
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 43 publications
6
24
0
2
Order By: Relevance
“…To our knowledge, this study is the first to describe a frontal plane as a best-fitting plane on an area on the manubrium (see Appendix). This consistent area appears to represent a structural adaptation of bone to mechanical loading as has been described in other bones 12,13 . This triangular area is based on the Y-shaped area that can be seen when placing the manubrium against a bright light or in a 3D CT-reconstructed manubrium.…”
Section: Image Analysis and Interpretationsupporting
confidence: 72%
“…To our knowledge, this study is the first to describe a frontal plane as a best-fitting plane on an area on the manubrium (see Appendix). This consistent area appears to represent a structural adaptation of bone to mechanical loading as has been described in other bones 12,13 . This triangular area is based on the Y-shaped area that can be seen when placing the manubrium against a bright light or in a 3D CT-reconstructed manubrium.…”
Section: Image Analysis and Interpretationsupporting
confidence: 72%
“…Though the right glenoid value was slightly more than the left, it was not statistically significant. Von Schroeder et al 8 , Coskun et al 9 and Karelse et al 10 reported the SI diameter to be 36±4mm, 36.3±3 mm and 35.9±3.6 mm respectively. All these values are higher than what was recorded in our study.…”
Section: Discussionmentioning
confidence: 96%
“…In the present study the average superiorinferior diameter of the right glenoid was 38.49±3.17mm and the average superior-inferior diameter of the left glenoid was38.06±3.34 mm. Von Schroeder et al [9], Coskun et al [16] and Karelse et al [12] [11] measured the SI diameter of the male and female glenoid separately. The average SI diameter of male glenoid measured by these authors was 37.5±2.2, 36.08±2.05 mm and 38.71±2.71mm respectively.…”
Section: Methodsmentioning
confidence: 99%